PTA of infrapopliteal arteries: long-term clinical follow-up and analysis of factors influencing clinical outcome - Peregrin, Jan H; Koznar, Boris; Kovác, Josef; Lastovicková, Jarmila; Novotný, Jirí; Vedlich, Daniel; Skibová, Jelena (Cardiovascular and interventional radiology, 2010)
This study was a retrospective analysis of patients with CLI who underwent infrapopliteal percutaneous transluminal angioplasty (PTA). The main goal was to evaluate clinical and morphological factors that influence the clinical outcome of PTA in long-term follow-up. A total of 1,445 PTA procedures were performed in 1,268 patients. Main indications for PTA included gangrene, nonhealing ulcers, or rest pain. The mean number of treated arteries was 1.77 artery/limb, and the majority of lesions were type TASC D. The technical success rate of PTA was 89% of intended-to-treat arteries. The main criterion of clinical success was functional limb salvage (LS). One-year follow-up involved 1,069 limbs. Primary and secondary 1-year LS rates were 76.1 and 84.4%, respectively. The effect of clinical and morphological parameters on the 1-year LS was that the only associated disease with an adverse effect on LS rate was DM combined with dialysis. Regarding limb preprocedural status, gangrene was clearly a negative predictor. The most important factor affecting LS was the number of patent arteries post-PTA: patients with 0, 1, 2, and 3 patent arteries had 1-year primary LS rates of 56.4, 73.1, 80.4, and 83%, respectively. Long-term follow-up of LS rates demonstrated secondary LS rates of 84.4, 78.8, and 73.3% at 1, 5, and 10 years. Every effort should be made to perform PTA for as many arteries as possible, even if TASC D type, to improve clinical outcome. Our study shows that repeat PTA is capable of keeping the long-term LS rate close to 75%.
Keywords: dospělí; Limb Salvage; Popliteal Artery; Endovascular Procedures; Kaplan-Meier Estimate; bérec; Female; endovaskulární výkony; Adult; Leg; výsledek terapie; ženské pohlaví; Kaplanův-Meierův odhad; mladý dospělý; Adolescent; průchodnost cév; lidé; arteria poplitea; Aged, 80 and over; následné studie; Treatment Outcome; Angioplasty; záchrana končetiny; retrospektivní studie; Follow-Up Studies; Male; Aged; Young Adult; angioplastika; Vascular Patency; lidé středního věku; Ischemia; senioři nad 80 let; ischemie; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Humans